Coup attempt restrictions (Turkey) - Voidly (Voidly Global Censorship Index, 2016)
CRITICAL severity censorship detected in Turkey. Data sourced from OONI.
Censorship Incident ID: TR-2016-0001. Severity: critical. Confidence: 90%